Throughput-Guaranteed Resource-Allocation Algorithms for Relay-Aided Cellular OFDMA System - Kaneko, M.; Popovski, P.; Hayashi, K. (IEEE transactions on vehicular technology, 2009)
Radio resource allocation for downlink transmissions in a cellular system based on orthogonal frequency-division multiple access (OFDMA) has been the subject of many research studies over the past few years. Nowadays, increasing attention has turned to cellular systems with relays, but only a few algorithms have been designed for OFDMA-based relay systems. In this paper, resource-allocation schemes are proposed for the cases of one relay station (RS) and multiple RSs in the cell. Due to the specific design of these algorithms, which operate in an RS-aided base station centralized manner, the amount of required channel-state information and algorithm complexity are minimized, making them suited for practical use. The idea of adaptive RS activation is introduced, where the frame structure is adapted depending on the active RS. Different numbers of relays are considered, and the corresponding algorithms are accordingly adapted. Simulation results show that our algorithms achieve a very good throughput/outage tradeoff.